Researcb on Social Network Collaborative Filtering Based E-commerce Recommending - Chunhua Ju; Fuguang Bao; Chonghuan Xu (Dianxin kexue)
With the development of the social network relation, whether the recommendation is successful, is not only depending on the characteristics of goods, but also influenced by social network relationship. Many users more trust from their friends'recommendation, rather than the machine recommended by single factor calculated results. Therefore, an E-commerce recommending system based on social network collaborative filtering was proposed. In the system, the crucial factors of social network relation intensity, interest preference intensity and production popularity with reputation intensity were set.And each first-level factor was composed of some second-level factors.Experimental results verify that social network relationships will affect users shopping behaviors and so on. In addition, the recommendation method based on social network is superior to other approaches and has better application effect.